Using Chemical Knowledge to Uncover New Biological Function: Discovery of the Cylindrocyclophane Biosynthetic Pathway - Nakamura, Hitomi; Balskus, Emily P. (Synlett, 2013)
An understanding of organic chemistry can play a central role in uncovering enzymes with new biochemical functions. We have recently identified the enzymes involved in the biosynthesis of the cylindrocyclophanes, a structurally unique family of natural products, and found that this pathway employs a remarkable macrocyclization event that requires functionalization of an unactivated carbon atom. This work illustrates the potential of using chemically guided approaches for enzyme discovery.
Keywords: biosynthesis; cylindrocyclophanes; natural products; enzymes; genomics